دور الإدارة الإلكترونية في تحسين الأداء الوظيفي للعاملين - علي سوفي; زعيم مسعودي (جامعة الوادي university of eloued, 2024)
"هدفت هذه الدراسة الى معرفة مفهوم الادارة الإلكترونية ودورها في تحسين الأداء الوظيفي للعاملين في بلدية قمار ولاية الوادي، والتعرف أيضا على بعض متطلبات الادارة الإلكترونية والتي تعتمد على تكنولوجيا المعلومات والاتصالات خاصة الانترنت والأجهزة والبرامج. ولتحقيق هدف هذه الدراسة تم الاعتماد على مجتمع الدراسة في بلدية قمار ولاية الوادي 2024 ، وهذا باستخدام أسلوب العينة العشوائية ولقد صممت استبيانة كأداة أساسية في هذه الدراسة لغرض جمع البيانات ومعالجتها باستخدام برنامج التحليل الاحصائي SPSS ، حين تم توزيع 50 إستبيانة على موظفي بلدية قمار ولاية الوادي، وقد تم استرجاع جميع الاستبيانات ولقد كان الهدف الرئيسي من هذه الدراسة هو وجود أثر للادارة الالكترونية في تحسين الأداء الوظيفي للعاملين في المؤسسة من وجهة نظر موظفي الموسسة المبحوثة. " "which aimed to know the concept of electronic management and its role in improving the job performance of workers in the municipality of Guemar in the El-Oued State, and also identify some of the requirements of electronic management, which depends on information and communications technology, especially the internet, hardware and software. To achieve the goal of this study, the study community was relied on in the municipality of Guemar, El-Oued State 2024. And this is using the random sample Method.a questionnaire was designed as a basic tool in this study for the purpose of collecting data and processing it using the SPSS statistical analysis program, when 50 questionnaires were distributed to employees of the municipality of Guemar, El-Oued State, all questionnaires were retrieved. The main goal of this study was the impact of electronic management in improving the job performance of employees in the institution from the point of view of the employees of the institution studied. "
Keywords: الإدارة الالكترونية ، الأداء الوظيفي للعاملين. electronic management; job performance of employees.